РОЛЬ И МЕСТО библиотеки в социокультурном пространстве (Библиосфера, 2011)
The functions of the culture and the essence of the social and cultural environment are treated, the role and place of a library as a social and cultural institution in forming the national-cultural identity of a personality are shown.